2016
DOI: 10.1037/pst0000090
|View full text |Cite
|
Sign up to set email alerts
|

Outcome differences between individual and group formats when identical and nonidentical treatments, patients, and doses are compared: A 25-year meta-analytic perspective.

Abstract: There are mixed findings regarding the differential efficacy of the group and individual format. One explanation of these mixed findings is that nearly all-recent meta-analyses use between-study effect sizes to test format equivalence introducing uncontrolled differences in patients, treatments, and outcome measures. Only 3 meta-analyses were located from the past 20 years that directly tested format differences in the same study using within-study effect sizes; mixed findings were reported with a primary limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 112 publications
7
55
1
5
Order By: Relevance
“…In two separate studies, researchers have found that group psychotherapy for panic disorder was more cost-effective than individual psychotherapy or pharmacotherapy (Otto et al, 2008;Roberge et al, 2008). In a study of children (Burlingame et al, 2016). In the three RCTs in the current metaanalysis that compared group and individual psychotherapy for EDs (Chen et al, 2003;Nevonen & Broberg, 2005, similar dropout rates were reported for both modalities.…”
Section: Benefits Of Group Psychotherapy For Eating Disorderssupporting
confidence: 62%
See 3 more Smart Citations
“…In two separate studies, researchers have found that group psychotherapy for panic disorder was more cost-effective than individual psychotherapy or pharmacotherapy (Otto et al, 2008;Roberge et al, 2008). In a study of children (Burlingame et al, 2016). In the three RCTs in the current metaanalysis that compared group and individual psychotherapy for EDs (Chen et al, 2003;Nevonen & Broberg, 2005, similar dropout rates were reported for both modalities.…”
Section: Benefits Of Group Psychotherapy For Eating Disorderssupporting
confidence: 62%
“…The findings indicate that group psychotherapy may be a suitable treat- (Burlingame et al, 2016). In the three RCTs in the current metaanalysis that compared group and individual psychotherapy for EDs (Chen et al, 2003;Nevonen & Broberg, 2005, similar dropout rates were reported for both modalities.…”
Section: Benefits Of Group Psychotherapy For Eating Disorderssupporting
confidence: 60%
See 2 more Smart Citations
“…Observed effects correspond to earlier bGT depression studies [40,41,74], to benchmarking meta analyses on group therapy [75][76][77], and to recent group therapy trials in routine care [78,79]. Moreover, the current study expands these findings by indicating high treatment effects in a comparably short period of time; as guideline-based group CBT usually entails 15 -20 hour sessions [33].…”
Section: Discussionsupporting
confidence: 51%